Nickel doped graphitic carbon nitride nanosheets and its application for dye degradation by chemical catalysis. (May 2018) - Das, D.; Banerjee, D.; Mondal, M.; Shett, A.; Das, B.; Das, N.S.; Ghorai, U.K.; Chattopadhyay, K.K.
Graphical abstract: Highlights: Nickel doped Graphitic carbon nitride (GCN) was synthesized chemically. Mott-Schottky was done to calculate the flat band potentials and donor densities of pure and doped samples. Toxic Methyl Orange dye was degraded efficiently by doped samples in the presence of NaBH4 accompanied by hydrogen evolution. Enhancement of catalytic activity with increasing doping concentration was studied in presence of varying amount of NaBH4 . A plausible mechanism for catalytic degradation was discussed in details. Abstract: A facile synthesis of transition metal-nickel doped graphitic carbon nitride (NiGCN) nanosheets with varying doping concentrations has been reported. X-Ray diffraction and Fourier transformed infrared spectroscopic study were performed to analyse the structural phase formation and different bonds present in the samples, whereas, field emission and transmission electron microscopic study provided the morphological information. The thermal stability of the samples was measured from the TG-DTA analysis. Photoluminescence spectroscopy was performed to elucidate the emissive property of the samples. The flat band potential of the samples was measured by Mott-Schottky analysis. First principle study was carried out to delineate the probable doping site of the Ni atom along with the effect of doping on the pure material. The samples were effectively utilized to degrade toxic methyl orange (MO) dye from water in the presence of sodium borohydride (NaBH4 ) without exploiting any visible light source. The plausible catalysis mechanism following a series of several chemical reactions has been discussed in details.